Fostering Active Citizenship: Facebook's Role in Youth Civic Engagement - Borrero, Juan Diego; Borrero-Domínguez, Encarna (Cuadernos.info, 2024)
Social media platforms (SMPs) have revolutionized social networks by facilitating connections and shaping the landscape of social interactions. The role of SMPs in contemporary civic participation, both online and offline, is undeniable. However, to understand the beliefs that drive young adults to use popular SMPs such as Facebook for civic engagement, fresh perspectives must be considered. This study extends the Unified Theory of Acceptance and Use of Technology (UTAUT) by conducting a questionnaire among 209 university students who actively use Facebook. Our results show that both expectancy and social influence gave a significant impact on students' intentions to use Facebook for civic engagement. We also identify Facebook mobilization efforts via smartphones as a strong predictor of both intention and use of Facebook for civic engagement. These findings indicate that Facebook is a valuable tool for young people to engage and participate in online social and political movements. While we acknowledge the limitations of this study, our analysis underscores the immense potential of SMPs as means for political participation.